2018
DOI: 10.1096/fj.201700598rrr
|View full text |Cite
|
Sign up to set email alerts
|

Vesicle‐mediated secretion of misfolded prion protein molecules from cyclosporin A‐treated cells

Abstract: Loss of protein homeostasis is a hazardous situation that jeopardizes cellular functionality and viability. Cells have developed mechanisms that supervise protein integrity and direct misfolded molecules for degradation. Nevertheless, subsets of aggregation-prone proteins escape degradation and form aggregates that can underlie the development of neurodegenerative disorders. In some cases, cells deposit hazardous protein aggregates in designated sites, like aggresomes, or secrete them with vesicles. The prion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Moreover, it was shown that these exosomal prion proteins retained their infectivity (Arellano-Anaya et al, 2015). Pan et al observed that prion proteins were secreted in exosomes upon inhibition of cyclophillins by the immunosuppressive agent cyclosporine A, which usually leads to an accumulation of aggregated PrP sc and its deposition in aggresomes in N2a and Chinese hamster ovary cells (Pan et al, 2018). The presented studies strongly indicate that different prion protein species are secreted via exosomes and therefore contribute, possibly to a high extent, to the spread of the misfolded, pathogenic protein in prion diseases.…”
Section: Prion Diseasesmentioning
confidence: 63%
“…Moreover, it was shown that these exosomal prion proteins retained their infectivity (Arellano-Anaya et al, 2015). Pan et al observed that prion proteins were secreted in exosomes upon inhibition of cyclophillins by the immunosuppressive agent cyclosporine A, which usually leads to an accumulation of aggregated PrP sc and its deposition in aggresomes in N2a and Chinese hamster ovary cells (Pan et al, 2018). The presented studies strongly indicate that different prion protein species are secreted via exosomes and therefore contribute, possibly to a high extent, to the spread of the misfolded, pathogenic protein in prion diseases.…”
Section: Prion Diseasesmentioning
confidence: 63%
“…The highest fold increase is seen in the cyclophilin family of peptidyl-prolyl isomerases PPIA, PPIB and FKBP2. Interestingly, inhibition or deficiency of PPIA results in increased aggregation and faster disease progression in models for prion disease [1,49]. Other, mainly ER resident, protein folding associated proteins maintain normal expression in GVD but decrease in tangle bearing neurons (Fig.…”
Section: Gvd Is Associated With Activation Of Protein Folding and Degradation And Dysregulation Of Rna Processingmentioning
confidence: 97%
“…Specifically, EVs have been linked to important biological functions, such as cell-to-cell signaling pathways associated with inflammatory responses and removal of aggregated and misfolded proteins within the brain (129,143). Moreover, EVs can cross the BBB and their membrane provides protection to proteins and nucleic acids, likely reducing their degradation in the peripheral circulation (163)(164)(165)(166).…”
Section: Extracellular Vesicles In Tbimentioning
confidence: 99%